History of Infectious Diseases in Toddlers and Frequency of Community Health Center Nutrition Services with Stunting Incidents - Suhartanti, Ika; Mawaddah, Nurul; Marwan, La (Jurnal Kesehatan Komunitas Indonesia, 2023)
Toddlers are an important period in the process of growth and development of a child. Malnourished children can experience malnutrition and this can result in stunting. Stunting incidents could have a negative impact on the growth and development period of toddlers. There were several factors that influenced the incidence of stunting, both directly and indirectly. Stunting was still a serious health problem facing Indonesia. This study aims to analyze the relationship between the history of infectious diseases and the frequency of community health centre nutrition services with the incidence of stunting. The research design was cross-sectional with a stratified simple random sampling technique taken from 8 posyandu (Integrated Healthcare Center) with a total sample of 112 toddlers. This research was conducted in the work area of the Saritani Community Health Center, Boalemo Regency, Gorontalo Province, from January to February 2023. The data analysis technique used in this research was the Chi-Square test. The results of the study showed that there was a significant relationship between the history of infectious diseases in toddlers and the incidence of stunting (p value=0.006; p-value ≤ α = 0.05), OR value=2.804 and there was a significant relationship between the frequency of health centre nutrition services and the incidence of stunting ( p value=0.001; p-value ≤ α = 0.05), OR value=2.859 in the working area of the Saritani Health Center, Boalemo Regency. Nurses can carry out health promotion efforts for mothers of toddlers to increase stunting prevention by knowing the factors that cause stunting. Increase efforts to provide nutritional education services related to stunting at community health centres, namely the First 1000 Days of Life, Infant and Child Feeding Practices, and routine exclusive breastfeeding.